Binomial R&D Races and Growth - John Hartwick (Queen's University, Department of Economics, 2004)
In each period, we have an R&D race among N competitive R&D firms, each with probability π of discovering a successful new technique for producing an intermediate good used in producing the economy's final consumption good. The winner of a race earns a monopoly profit over a generally uncertain interval. Each R&D firm faces distinctive "lottery" and "duration" uncertainty in each period. Numerical examples illustrate the growth behavior of the economy linked to the R&D sector.
Keywords: O41; O31; 330; binomial R&D race; growth